IDENTIFIKASI MOLEKULAR DAN KARAKTERISASI MORFO-FISIOLOGI ACTINOMYCETES PENGHASIL SENYAWA ANTIMIKROBA - Nurkanto, Arif; Agusta, Andria (JURNAL BIOLOGI INDONESIA, 2015)
ABSTRACTThe objectives of study were to identify antimicrobial producing Actinomycetes using 16S rDNA analyses and morphology and physiology characteristics. Eight Actinomycetes strain with the higest antibacterial and antifungal activity were selected and identified using six primers (20F, 520F, 920F, 1500R, 920R, and 520R). Morphological observation and physiology analyses were performed to the selected strain to accurately identify the strains. Morphological characters observed were aerial mycelium, spore chain, colony form, and pigment production. Physiological characterizations were antimicrobial properties, growth temperature, pH tolerance, salinity concentration for growth, sugars assimilation, and some enzymes production (arginine dihydrolase, urease, ß-glucosidase, protease, ß-galactosidase). Based on homology search by BLAST program and phylogenetic tree analyses, all of isolates were identified as the genus Streptomyces. They belong to eight different spesies. Isolates RC-SS-37-4, RC-SS-37-16 and BL-22-3 have been identified as Streptomyces costaricanus (100 %), Streptomyces costaricanus (99.8 %) and Streptomyces parvulus (98.6 %), respectively. Five isolates were identified as Streptomyces spp. (BL-36-1, BL-20-2, BL-14-2, BL-22-1 and BL-06-5) and can be presumed as new species because of the low homology value to their closest related spesies. Keywords : actinomycetes, antimicrobial, morphology, phylogenetic, physiology, 16S rRNA gene.